Automatic Detection of Lupus Butterfly Malar Rash Based on Transfer Learning - Souza, Jhonatan; de Oliveira, Tiago; Casa, Claudemir; Ortoncelli, André (Anais do Workshop de Visão Computacional (WVC), 2020)
This work presents an approach to the automatic detection of Butterfly Malar Rash (BMR) in images. BMR is a Lupus symptom characterized by a reddish facial rash that appears symmetrically in the cheeks and the back of the nose. The proposed approach is based on Transfer Learning, a popular approach in Deep Learning that consists in the use of pre-trained models as the starting point for computer vision and natural language processing tasks. To perform the experiments, a database was created with images manually collected from the Instagram social network, searching for images with #butterflyrash. We evaluated the proposed approach with eight Convolutional Neural Networks (CNN) architecture. The experimental results are good results, with a precision of up to 0.957.